DC distribution grid and the associated advanced DC/DC converter - Swaisi, Mahmoud (2017)
AC or DC has been in the centre of debate since the early days of the electrical system. DC is already proven to be more economical than AC in transmission at elevated power and voltages. Thus, expanding the use of DC to the distribution grids seems promising as most of the distributed generation such as PV generates initial DC voltages and many of the modern loads are using internal DC buses. Still, in order to extend the use of DC to the distribution level a suitable DC distribution grid architecture and a suitable DC/DC converter to serve it should be explored, which is the focus of this Ph.D. A study based on the Libyan grid and loads was carried out to investigate the most suitable DC distribution grid layout. The results showed that DC grid arrangement utilising two port converters have lower total converter losses and smaller converter installed power when compared with arrangements using three ports converter. A multi-cell multi–snubbered three phase dual active bridge (DAB) converter was proposed to serve the chosen DC distribution grid layout. The modular multi-cell multi–snubbered 3 phase DAB converter offered low losses over a wide range of loading profiles. Furthermore, the converter performance can be easily modified to be able to serve a specific DC/DC grid loading profile by altering the snubbers attached to the cells and the power management’s algorithm between the cells while keeping the core cells the same. Extra cells can be added if higher power rating is required, reducing the total cost of expanding the proposed DC distribution system. This thesis is an ambition step on deciding the structure of the futuristic DC grid and the required DC/DC converters to link it is different voltage levels.